(untitled) (Universidad de San Andres Law Review, 2022)
The current state of the debate on the liability of Internet search engines will be examined. Given the absence of specific regulation, we will resort to general guidelines of civil liability and its harmonic application with the constitutional guarantees involved, treating the legal system as a whole, avoiding the use of traditional watertight compartments. Within this framework, the different theories that have been outlined in Argentine law, national and foreign jurisprudence will be discussed, in order to understand the options available to the Supreme Court at the time of deciding in the case "Rodríguez, María Belén v. Google Inc. and others s/damages". As regards the conflicts that may arise in the matter to be dealt with, the article will focus on the possible infringement of personal rights, such as honor or privacy.